Numerical Reconstruction of Small Perturbations in the Electromagnetic Coefficients of a Dielectric Material (Journal of Computational Mathematics, 2018)
The aim of this paper is to solve numerically the inverse problem of reconstructing small amplitude perturbations in the magnetic permeability of a dielectric material from partial or total dynamic boundary measurements. Our numerical algorithm is based on the resolution of the time-dependent Maxwell equations, an exact controllability method and Fourier inversion for localizing the perturbations. Two-dimensional numerical experiments illustrate the performance of the reconstruction method for different configurations even in the case of limited-view data.
Keywords: Maxwell's equations; Inverse problems; Numerical reconstruction; Exact boundary controllability; Fourier inversion.